Semantic Shifts of English Technological Terms in Uzbek Media - Kholmurodova , Zarina; Dalieva , Madina Khabibullaevna (The Lingua Spectrum, 2026)
In recent years, rapid technological advancement has significantly increased global communication and widespread adoption of English technological terminology between different languages, including Uzbek. This article investigates the semantic shifts of English technological terms in Uzbek media discourse. The study examines several examples of active usage of English terms from online newspapers, social media sites, and technology news portals. It is indicated that when technological terms are adopted into Uzbek media language, they often go through semantic changes such as broadening, narrowing and metaphorical extension. In many cases, borrowed words adjust to the Uzbek language’s lexicon and get new conceptual meanings. In other words, currently, Uzbek media – including television programs, blogs, news websites and social media – frequently use English-derived terms such as “platform”, “blog”, “trend”, “content”, “channel” which have acquired extra semantic complexities in Uzbek media usage. The study emphasizes how the media shapes new semantic interpretations of borrowed terminology and disseminates technology language. The findings provide explanations with knowledge of lexical borrowing and semantic transformation in today’s Uzbek language use.